Effect of Herbal, Homeopathic and Hormonal Drug on Hematology, Ovarian Cyclicity and Conception Rate in Postpartum Anoestrus Cows - Kumar, Jitendra; Srivastava, Sushant; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study was designed to assess the effect of herbal, homeopathic, and hormonal drugs namely Janova, Sepia and GnRH-PG-GnRH on hematological parameters, resumption of ovarian cyclicity and conception rate in 40 postpartum anoestrus and 8 normal cyclic cows. The anoestrus cows were randomly divided into five groups as G0, GI, GII, GIII, GIV; 8 cows in each group. Group G0 (untreated anoestrus) and GV (normal cyclic cows) served as positive and negative control, respectively. All cows in GI, GII, GIII and GIVwere subjected to dewormer and mineral mixture supplementation for 10 days, while group GII, GIII, and GIV were additionally treated with Janova (herbal heat inducer), Sepia (a homeopathic drug) and GnRH-PG-GnRH (Ovsynch) protocol, respectively. Different therapeutic protocols revealed variable and significant effects on most of the hematological parameters, except differential leucocyte count, before and after treatment. The values were also significantly higher in normal cyclic than anoestrus groups. The oestrus induction response in G0, GI, GII, GIII, GIV, and GVwas 0.00, 50.00, 62.50, 75.00, 87.50, and 100.00 %, and corresponding overall conception rates of 3 cycles were 0.00, 75.00, 80.00, 66.66, 57.13 and 75.00 %, respectively. In conclusion, aforesaid therapeutic regimens have definite bearings on oestrus induction as well as on conception and can be used to manage postpartum anoestrus in cows.